Nitrogen dioxide, an EPA parameter, may forecast the incidence of asthma exacerbations across urban areas: An observational study. Issue 1 (14th October 2022) - Solanki, Neha; Bruckman, David; Wang, Xiaofeng; Tang, Anne; Attaway, Amy; Khatri, Sumita
Abstract: Rationale: Efforts to reduce nitrogen dioxide (NO2 ) have the potential to reduce the morbidity and mortality related to asthma in children. We analyze the associations of pediatric hospital admission rates for asthma with Environmental Protection Agency (EPA) NO2  parameters at the patient zip code level. Methods: We identified zip codes that had EPA monitors which monitored NO2  levels located in states with high asthma burden. We used the Healthcare Cost and Utilization Project (HCUP) State Inpatient Database (SID) to identify patients who were <17 years of age with diagnosis codes for asthma. We compared NO2  levels at the zip code level with the number of patients hospitalized for asthma from the HCUP SID database. Results: Data from zip codes in Buffalo, Detroit, Phoenix, and Tucson from 2009 to 2011 demonstrated that the monthly mean NO2  levels predicted pediatric asthma hospital admission rates in six monitored zip codes in these four cities with time series modeling (Buffalo zip code 14206, p  = 0.0089; Detroit zip code 48205, p  = 0.0179; Phoenix zip code 85006, p  = 0.0433; Phoenix zip code 85009, p  = 0.0007; Phoenix zip code 85015, p  = 0.0036; Tucson zip code 85711, p  = 0.0004). Conclusion: Pediatric admissions to the hospital for asthma exacerbations mirror the cyclic and seasonal pattern of NO2  levels in the cities of Detroit, Buffalo, Phoenix, and Tucson. While traffic density may be higher in cities with periodicity of NO2  and asthma exacerbations, other factors could be contributing to high NO2  levels.